A new species of Procanace Hendel from the Philippines (Diptera: Canacidae: Canacinae) - Munari, Lorenzo (Zootaxa, 2022)
A new species of surf flies (Canacidae: Canacinae) is described and illustrated based on four specimens (1 ♂, 3 ♀) collected by Dr. Amnon Freidberg in the Philippines. Some peculiarities of the postabdominal structures, especially those of the male terminalia, suggest a fairly close affinity with two other congeneric species, namely Procanace townesi Wirth, 1951, and P. cogani Mathis, 1988, having a disjointed distribution, Marshall Islands and Seychelles, respectively. It is further suggested that these affinities should arguably be regarded as synapomorphic character states in the groundplan of the genus.